Tax Amnesty : Kajian Program Amnesti Pajak Indonesia - Harun Ongah (Forum Kerjasama Pendidikan Tinggi, 2024)
Tax is one of a country’s income which is used to improve the citizen’s prosperity. However, tax evasion has been rampant and could reduce tax income and eventually harming the country’s economy. Consequently, the government of the Republic of Indonesia has organized several tax amnesty programs to allow taxpayers to report their hidden asset without being punished. This article aimed to review all the tax amnesty policy that has been conducted in Indonesia thus far. This article also delved into other countries tax amnesty programs to allow the understanding of the short-term and long-term possible effects which may occur. Although the 1964 and 1984 tax amnesty program were deemed fail, the 2016-2017 tax amnesty and the voluntary recognition program in 2022 managed to boost the country’s short-term tax income. The 2016-2017 program even breaks the world record for the number of taxes collected from a single tax amnesty program. Nevertheless, the long-term effect, such as the decline in taxpayer’s compliance and the country’s economy must be considered. Unfairness towards compliant taxpayers must also be considered as it may reduce compliance in future payment. Future tax amnesty program, especially the one that is planned to be conducted in 2025, must be consider the possible negative aspect as well as other countries experience with tax amnesty.